Pengukuran Kadar Kolesterol Total Dan Pelayanan Konsultasi Sindrom Metabolik Di Kelurahan Rawamangun, Jakarta Timur - Astri Handayani; Fransisca Chondro; Lily Marliany Surjadi; Juni Chudri (AMMA : Jurnal Pengabdian Masyarakat, 2023)
Metabolic syndrome is a set of symptoms of metabolic disorders consist of insulin resistance, dyslipidemia, central obesity and hypertension. Metabolic syndrome can be categorized as an important problem for pre-elderly and elderly age groups, due to the aging process factors that play an important role in the prevalence of cardiovascular risk and metabolic risk factors. One indicators to check is the cholesterol level. Cholesterol levels that exceed normal level in the body will accumulate in the walls of blood vessels and cause a condition called atherosclerosis. Based on the above, it is considered necessary to check the level of total cholesterol in the blood as a simple initial screening step for metabolic syndrome and conduct management and lifestyle changes. This community service activity will be done with consultation, screening, physical examination and treatment of residents. A supporting examination will be conducted to find out the total cholesterol level. Then the participants consult according to the examination results.